Perceptions in litigation and mediation : lawyers, defendants, plaintiffs, and gendered parties / Tamara Relis. - Relis, Tamara (Cambridge University Press, 2009)
Offering interdisciplinary insights from sociological, psychological and gender studies, this book addresses this question: how do professional, lay and gendered actors understand and experience case processing in litigation and mediation? Drawing on data from 131 interviews, questionnaires and observations of plaintiffs, defendants, lawyers and mediators involved in 64 fatality and medical injury cases, the book challenges dominant understandings of how formal legal processes and dispute resolution work in practice as well as the notion that disputants and their representatives broadly understand and want the same things during case processing. In juxtaposing actors' discourse on all sides of ongoing cases on issues such as expectations, needs, comprehensions of what plaintiffs seek from the legal system, objectives for resolving conflict at mediation, and perceptions of what occurs during attempts at case resolution, the findings reveal inherent problems with the core workings of the legal system.